Đang tải thanh công cụ tìm kiếm ...
Phép Tính Online

Tính đạo hàm của các hàm số sau

Tính đạo hàm của các hàm số sau

a) \(y = 2\sqrt x {\mathop{\rm sinx}\nolimits}  - {{\cos x} \over x}\)                                   

b) \(y = {{3\cos x} \over {2x + 1}}\)

c) \(y = {{{t^2} + 2\cot t} \over {\sin t}}\)                                                

d) \(y = {{2\cos \varphi  - \sin \varphi } \over {3\sin \varphi  + \cos \varphi }}\)

e) \(y = {{\tan x} \over {\sin x + 2}}\)                                                  

f) \(y = {{\cot x} \over {2\sqrt x  - 1}}\)

Trả lời:

a)

\(y' = (2\sqrt x {\mathop{\rm sinx}\nolimits}  - {{\cos x} \over x})'\)

\(\eqalign{
& = 2{1 \over {2\sqrt x }}\sin x + 2\cos x - {{ - \sin x - \cos x} \over {{x^2}}} \cr
& = {{x\sqrt x \sin x + 2{x^2}\cos x + x\sin x + \cos x} \over {{x^2}}} \cr
& = {{x(\sqrt x + 1)\sin x + (2{x^2}\sqrt x + 1)cosx} \over {{x^2}}} \cr} \)

b)

\(\eqalign{
& y' = ({{3\cos x} \over {2x + 1}})' = {{ - 3(2x + 1)\sin x - 2.3\cos x} \over {{{(2x + 1)}^2}}} \cr
& = {{ - 3(2x + 1)\sin x - 6\cos x} \over {{{(2x + 1)}^2}}} \cr} \)

c)

\(\eqalign{
& y' = ({{{t^2} + 2\cot t} \over {\sin t}})' = {{(2t - 2\sin t)\sin t - \cos t({t^2} + 2\cos t)} \over {{{\sin }^2}t}} \cr
& = {{2t\sin t - 2{{\sin }^2}t - {t^2}\cos t - 2{{\cos }^2}t} \over {{{\sin }^2}t}} \cr
& = {{2t\sin t - {t^2}\cos t - 2({{\sin }^2}t + {{\cos }^2}t)} \over {{{\sin }^2}t}} = {{2t\sin t - {t^2}\cos t - 2} \over {{{\sin }^2}t}} \cr} \)

d)

\(\eqalign{
& y' = ({{2\cos \varphi - \sin \varphi } \over {3\sin \varphi + \cos \varphi }})' \cr
& = {{( - 2sin\varphi - \cos \varphi )(3sin\varphi + \cos \varphi ) - (3\cos \varphi - \sin \varphi )(2\cos \varphi - \sin \varphi )} \over {{{(3\sin \varphi + \cos \varphi )}^2}}} \cr
& = {{ - 7} \over {{{(3\sin \varphi + \cos \varphi )}^2}}} \cr} \)

e)

\(\eqalign{
& y' = ({{\tan x} \over {\sin x + 2}})' = {{{1 \over {{{\cos }^2}x}}(\sin x + 2) - \cos x\tan x} \over {{{(\sin x + 2)}^2}}} = {{{1 \over {{{\cos }^2}x}}(\sin x + 2) - \sin x} \over {{{(\sin x + 2)}^2}}} \cr
& = {{\sin x + 2 - \sin x{{\cos }^2}x} \over {{{\cos }^2}x{{(\sin x + 2)}^2}}} = {{\sin x(1 - {{\cos }^2}x) + 2} \over {{{\cos }^2}x{{(\sin x + 2)}^2}}} = {{{{\sin }^3}x + 2} \over {{{\cos }^2}x{{(\sin x + 2)}^2}}} \cr} \)

f) 

\(\eqalign{
& y' = ({{\cot x} \over {2\sqrt x - 1}})' = {{(\cot x)'(2\sqrt x - 1) - \cot x(2\sqrt x - 1)'} \over {{{(2\sqrt x - 1)}^2}}} = {{{{ - 1} \over {{{\sin }^2}x}}(2\sqrt x - 1) - \cot x.{1 \over {\sqrt x }}} \over {{{(2\sqrt x - 1)}^2}}} \cr
& = {{{{1 - 2\sqrt x } \over {{{\sin }^2}x}} - {{\cot x} \over {\sqrt x }}} \over {{{(2\sqrt x - 1)}^2}}} \cr} \)